SAT0409 Association between Tobacco Smoking and Response to Tumor Necrosis Factor Alpha Inhibitor Treatment in Psoriatic Arthritis: Results from the Danbio Registry. (10th June 2014) - Højgaard, P.; Glintborg, B.; Hetland, M.L.; Hansen, T.H.; Nilsson, C.; Lage-Hansen, P.R.; Petersen, M.H.; Holland-Fisher, M.; Loft, A.G.; Andersen, B.N.; Adelsten, T.; Jensen, J.; et al.
Abstract : Background: Identification of response modifiers to tumor necrosis factor alpha inhibitors (TNFi) will facilitate an effective and rational treatment strategy. In rheumatoid arthritis smoking has been shown to reduce treatment response to TNFi while the impact of smoking is sparsely investigated in psoriatic arthritis (PsA). Objectives: To investigate the association between tobacco smoking and disease activity, treatment adherence and treatment responses among patients with psoriatic arthritis (PsA) initiating the first tumor necrosis factor alpha inhibitor therapy (TNFi) in routine care. Methods: Observational cohort study based on the nationwide Danish DANBIO registry. Kaplan-Meier plots, logistic and Cox regression analyses by smoking status were calculated for treatment adherence, ACR20/50/70-responses and EULAR-good-response. Results: Among 1388 PsA patients included in the study, 1148 (83) had known smoking status (33% current, 41% never and 26% previous smokers). Median follow-up time was 446 days (interquartile-range, IQR 161-1082). At baseline, current smokers had lower body mass index (27 kg/m 2 (23-30)/28 kg/m 2 (24-31)) (median (IQR)), shorter disease duration (3 years (1-8)/5 years (2-10)), lower swollen joint count (2 (0-5)/3 (1-6)), higher visual-analogue-scale (VAS) patient global (72 mm (54-87)/68 mm (50-80)), VAS fatigue (72 mm (51-86)/63 mm (40-77)) and Health Assessment Questionnaire (HAQ) score (1.1 (0.7-1.5)/1.0 (0.5-1.5)) than never smokers (all p<0.05). Current smokers had poorer 50% treatment adherence than never smokers (1.56 years (0.97-2.15)/2.43 years (1.88-2.97), (median (95%CI)), log rank p=0.02) and poorer 6 months' EULAR-good response rates (23%/34%), ACR20 (24%/33%) and ACR50 response rates (17%/24%) (all p<0.05), most pronounced in men. In current smokers the treatment adherence was poorer for infliximab (hazard ratio (HR) 1.62, 95%CI 1.06-2.48) and etanercept (HR 1.74, 1.14-2.66) compared to never smokers, but not for adalimumab (HR 0.80, 0.52-1.23). Conclusions: Current smoking was associated with poorer patient-reported outcomes, treatment adherence and clinical response in TNFi treatment of PsA. This was most pronounced in men and in patients treated with infliximab and etanercept. Acknowledgements: Thanks to all departments of rheumatology in Denmark for reporting to the DANBIO registry. Disclosure of Interest: P. Højgaard: None declared, B. Glintborg: None declared, M. Hetland: None declared, T. Hansen: None declared, C. Nilsson: None declared, P. Lage-Hansen: None declared, M. Petersen: None declared, M. Holland-Fisher Paid instructor for: UCB, MSD, Roche, Speakers bureau: UCB, MSD, Roche, A. G. Loft Grant/research support: Wyeth, Paid instructor for: AbbVie, MSD, B. Andersen: None declared, T. Adelsten: None declared, J. Jensen: None declared, E. Omerovic: None declared, R. Christensen: None declared, U. Tarp: None declared, R. Østgaard: None declared, L. Dreyer: None declared DOI: 10.1136/annrheumdis-2014-eular.2326